EVALUASI KELAYAKAN PENDANAAN PROYEK DENGAN TEKNIK PEMROGRAMAN LINIER - Partono, Windu (TEKNIK, 2007)
One main problem characterizes linear programming is to seek the maximum or minimum of a linearexpression when the variables of the problem are subject to restrictions in the form of certain linearequalities or inequalities. Problems of this kind are encountered when we have to exploit limitedresources in an optimal way. Project Cost Evaluation which play an important role in project are ofspecial significance in this respect. The real problem of Project Cost Evaluation analysis are tomanipulate cash flow problems of project into linear programming model or mathematical model.This method should be selected technically according the actual condition of the project. In designingand selecting the mathematical models, it is necessary to take into consideration the relationshipbetween the limited resources (money) and the optimal solution.